Hospitality, Subjectivity and Ceremony: Glee Confronts Hetero-normativity - Anne Cranny-Francis (Law Text Culture, 2014)
As Matei Candea and Giovanni da Col note in their Preface to a special issue of the Journal of the Royal Anthropological Institute (2012), the last decade has seen a resurgence of interest in the notion of hospitality: From Levinas’s phenomenological ethics and Serres’s study of parasitic relationships, through to Agamben’s musings on ‘inclusive exclusion’ and Derrida’s invention of the neologism hostipitality’ (ii). They note also that political, literary and legal scholars have approached this topic through studies of the roles of host and guest, which has led to theorizations of related concerns including migration, postcoloniality, sovereignty and international law. This article also approaches the concept of hospitality by analyzing the roles of host and guest in a specific text, namely, an episode of the television series, Glee (2009–). My interest is how the characters in the episode articulate and embody these roles, and how their interactions are used to challenge conventional understandings of subjectivity and of hospitality. In particular, I consider their characterization by reference to Jean-Luc Nancy’s notion of being as always fundamentally relational (being-with) and as always negotiated in relation to others (being singular plural). (Nancy 2000: 30)